How Neuroscience and Behavioral Genetics Improve Psychiatric Assessment: Report on a Violent Murder Case - Rigoni, Davide; Pellegrini, Silvia; Mariotti, Veronica; Cozza, Arianna; Mechelli, Andrea; Ferrara, Santo Davide; Pietrini, Pietro; Sartori, Giuseppe (Frontiers in Behavioral Neuroscience, 2010)
Despite the advances in the understanding of neural and genetic foundations of violence, the investigation of the biological bases of a mental disorder is rarely included in psychiatric evaluation of mental insanity. Here we report on a case in which cognitive neuroscience and behavioral genetics methods were applied to a psychiatric forensic evaluation conducted on a young woman, J.F., tried for a violent and impulsive murder. The defendant had a history of multidrug and alcohol abuse and non-forensic clinical evaluation concluded for a diagnosis of borderline personality disorder. We analyzed the defendant’s brain structure in order to underlie possible brain structural abnormalities associated with pathological impulsivity. Voxel-Based Morphometry indexed a reduced gray matter volume in the left prefrontal cortex, in a region specifically associated with response inhibition. Furthermore, J.F.’s DNA was genotyped in order to identify genetic polymorphisms associated with various forms of violence and impulsive behaviour. Five polymorphisms that are known to be associated with impulsivity, violence, and other severe psychiatric illnesses were identified in J.F.’s DNA. Taken together, these data provided evidence for the biological correlates of a mental disorder characterized by high impulsivity and aggressive tendencies. Our claim is that the use of neuroscience and behavioral genetics do not change the rationale underlying the determination of criminal liability, which must be based on a causal link between the mental disorder and the crime. Rather, their use is crucial in providing objective data on the biological bases of a defendant’s mental disorder.